2018
DOI: 10.3390/toxins10100408
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of JZTx-14, a Potent Antagonist of Mammalian and Prokaryotic Voltage-Gated Sodium Channels

Abstract: Exploring the interaction of ligands with voltage-gated sodium channels (NaVs) has advanced our understanding of their pharmacology. Herein, we report the purification and characterization of a novel non-selective mammalian and bacterial NaVs toxin, JZTx-14, from the venom of the spider Chilobrachys jingzhao. This toxin potently inhibited the peak currents of mammalian NaV1.2–1.8 channels and the bacterial NaChBac channel with low IC50 values (<1 µM), and it mainly inhibited the fast inactivation of the NaV1.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Furthermore, the toxin delayed the fast inactivation along with the reduction of peak currents in hNa V 1.1, hNa V 1.3 and hNa V 1.5 [92]. Such subtype-varying profiles have also recently been reported for Pn3a ( Pamphobeteus nigricolor ) [61], Pre1a ( Psalmopoeus reduncus) [111] and JzTx-14 ( C. jingzhao ) [125]. These multi-site effects of spider knottins on Na V channels need to be carefully considered when establishing their pharmacological profiles.…”
Section: Spider-venom Ick Peptidesmentioning
confidence: 66%
See 3 more Smart Citations
“…Furthermore, the toxin delayed the fast inactivation along with the reduction of peak currents in hNa V 1.1, hNa V 1.3 and hNa V 1.5 [92]. Such subtype-varying profiles have also recently been reported for Pn3a ( Pamphobeteus nigricolor ) [61], Pre1a ( Psalmopoeus reduncus) [111] and JzTx-14 ( C. jingzhao ) [125]. These multi-site effects of spider knottins on Na V channels need to be carefully considered when establishing their pharmacological profiles.…”
Section: Spider-venom Ick Peptidesmentioning
confidence: 66%
“…Spider knottins include a growing number of depressant toxins, including JzTx-V ( C. jingzhao ), Df1a ( D. fasciatus ), Pre1a ( P. reduncus ), PnTx4(5-5) from P. nigriventer , CcoTx-1 ( Ceratogyrus cornuatus ), PaurTx ( Phrixotrichus auratus) and Cd1a ( Ceratogyrus darlingi ) which induce a depolarizing shift in voltage-dependence of activation at specific Na V subtypes [73,79,92,107,110,111]. However, a number of spider depressant knottins reduced the sodium currents without changing the activation or inactivation kinetics (e.g., HwTx-IV, HnTx-III, HnTx-IV) [114,116,129], by shifting activation and inactivation to hyperpolarizing potentials (e.g., Df1a) [92] or by inhibiting both activation and inactivation (e.g., JzTx-14) [125]. Spider knottins (e.g., JzTx-V) also altered the slope factor of activation and inactivation associated to shifts in their voltage dependence [79,91] suggesting cooperativity between the four S4 segments or multiple binding sites [9,91].…”
Section: Spider-venom Ick Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously purified two potent gating-modifier toxins, JZTx-27 and JZTx-14, from the venom of spider Chilobrachys jingzhao . These toxins interact with the S3–S4 loop region of NaChBac and inhibit the channel activity by impeding voltage-sensor activation ( Tang et al, 2017 ; Zhang et al, 2018 ). A recent study testing the activity of several known peptide modulators of mammalian Na V channels showed that the site 4 toxins GsAF-I, GrTx1, and GsAF-II also effectively inhibit NaChBac currents, possibly by affecting the voltage-dependent gating of the channel ( Zhu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%